2016
DOI: 10.1021/acsnano.5b08057
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Up Nanofabrication of Supported Noble Metal Alloy Nanoparticle Arrays for Plasmonics

Abstract: Mixing different elements at the nanoscale to obtain alloy nanostructures with fine-tuned physical and chemical properties offers appealing opportunities for nanotechnology and nanoscience. However, despite widespread successful application of alloy nanoparticles made by colloidal synthesis in heterogeneous catalysis, nanoalloy systems have been used very rarely in solid-state devices and nanoplasmonics-related applications. One reason is that such applications require integration in arrays on a surface with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
141
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(151 citation statements)
references
References 48 publications
(114 reference statements)
5
141
0
Order By: Relevance
“…[12][13][14][15] Thus, metallic nanostructures composed of Ag-Au can enable the rational design of building blocks for different applications, such as metamaterials, [16,17] hot carrier devices, [18] light absorption improvement in photovoltaics, [19,20] colored glasses, [21] displays, [22,23] and catalysis. Alloying of these noble metals has been applied to tune the material dielectric function, where the LSPR can be modulated progressively from the UV (pure Ag) to the NIR (pure Au).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15] Thus, metallic nanostructures composed of Ag-Au can enable the rational design of building blocks for different applications, such as metamaterials, [16,17] hot carrier devices, [18] light absorption improvement in photovoltaics, [19,20] colored glasses, [21] displays, [22,23] and catalysis. Alloying of these noble metals has been applied to tune the material dielectric function, where the LSPR can be modulated progressively from the UV (pure Ag) to the NIR (pure Au).…”
mentioning
confidence: 99%
“…[24] To date, different fabrication techniques have been successfully utilized to realize Ag x Au 1−x alloyed NPs. [13] Nevertheless, this technique is constrained to specific applications due to its high cost and very limited scalability. However, the overall size of the NPs cannot be varied beyond 150 nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Au, Ag, and Pd, they all possess an fcc crystallographic Metals 2017, 7, 472 4 of 20 structure with complete miscibility, and thus the composite AuAgPd alloy nanostructures can be fabricated by sufficient dewetting and inter-mixing at a certain temperature [30]. Previous studies have shown the fully inter-mixed AuAgPd alloy NPs from the evaporation deposited tri-layers of~25 nm thickness by heating to~500 • C [31]. The surface morphology of the as-deposited ( Figure A2) uniform tri-layers was gradually transformed by the evolution of voids and nanoclusters at a relatively low temperature, and then isolated NPs at high temperature, as seen in Figure 1c,d.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Further, GaAs on Au has been experimentally reported to absorb 96% of incident light at λ = 38 µm. [29][30][31][32][33][34] Specifically, the alloying of metals has allowed materials with optical responses unachievable by the individual metal components. [29][30][31][32][33][34] Specifically, the alloying of metals has allowed materials with optical responses unachievable by the individual metal components.…”
mentioning
confidence: 99%